2019
DOI: 10.1038/s41594-019-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the otopetrin proton channels Otop1 and Otop3

Abstract: Otopetrins (Otop1–Otop3) comprise one of two known eukaryotic proton-selective channel families. Otop1 is required for otoconia formation and a candidate mammalian sour taste receptor. Here we report cryo-EM structures of zebrafish Otop1 and chicken Otop3 in lipid nanodiscs. The structures reveal a dimeric architecture, with each subunit forming twelve transmembrane helices divided into structurally similar amino (N) and carboxy (C) domains. Cholesterol-like molecules occupy various sites in Otop1 and Otop3 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 65 publications
1
61
0
Order By: Relevance
“…In contrast, Otop1 is well established to function as a proton channel in heterologous cells [34]. Moreover, cryoelectron microscopy (cryo-EM) studies have revealed the structure of the Otop1 channel [58], allowing an understanding of how proton selectivity is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Otop1 is well established to function as a proton channel in heterologous cells [34]. Moreover, cryoelectron microscopy (cryo-EM) studies have revealed the structure of the Otop1 channel [58], allowing an understanding of how proton selectivity is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, the bound density is either cholesterol, co-purified from the native bilayer 2426 , or may correspond to cholesterol derivatives such as cholesterol-hemisuccinate (CHS), which are added during purification 27,28 . Often multiple cholesterol binding sites are observed within the same structure 25 . For example a recent structure of the serotonin receptor, 5-HT 1A (Protein Databank (PDB) ID: 7E2X), revealed 10 cholesterol molecules surrounding the TMD, including one partially buried cholesterol adjacent to the orthosteric ligand pocket 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Sea urchin Alx1 also provides positive inputs directly into otop2L, the single sea urchin ortholog of the vertebrate otopetrin genes (Rafiq et al, 2014;Khor et al, 2019). Otopetrins are multi-pass transmembrane proteins that function as proton channels (Saotome et al, 2019). In vertebrates, these proteins play an essential role in regulating the timing, size, and shape of the developing otoconia, extracellular calcium carbonate biominerals that are required for vestibular functions (Hughes et al, 2004;Sollner et al, 2004;Kim et al, 2010).…”
Section: Otopetrinmentioning
confidence: 99%